Temperature-Sensitive Growth and Decreased Thermotolerance Associated with relA Mutations in Escherichia coli - Yang, Xiaoming (American Society for Microbiology, 2003)
The relA gene of Escherichia coli encodes guanosine 3′,5′-bispyrophosphate (ppGpp) synthetase I, a ribosome-associated enzyme that is activated during amino acid starvation. The stringent response is thought to be mediated by ppGpp. Mutations in relA are known to result in pleiotropic phenotypes. We now report that three different relA mutant alleles, relA1, relA2, and relA251::kan, conferred temperature-sensitive phenotypes, as demonstrated by reduced plating efficiencies on nutrient agar (Difco) or on Davis minimal agar (Difco) at temperatures above 41°C. The relA-mediated temperature sensitivity was osmoremedial and could be completely suppressed, for example, by the addition of NaCl to the medium at a concentration of 0.3 M. The temperature sensitivities of the relA mutants were associated with decreased thermotolerance; e.g., relA mutants lost viability at 42°C, a temperature that is normally nonlethal. The spoT gene encodes a bifunctional enzyme possessing ppGpp synthetase and ppGpp pyrophosphohydrolase activities. The introduction of the spoT207::cat allele into a strain bearing the relA251::kan mutation completely abolished ppGpp synthesis. This ppGpp null mutant was even more temperature sensitive than the strain carrying the relA251::kan mutation alone. The relA-mediated thermosensitivity was suppressed by certain mutant alleles of rpoB (encoding the β subunit of RNA polymerase) and spoT that have been previously reported to suppress other phenotypic characteristics conferred by relA mutations. Collectively, these results suggest that ppGpp may be required in some way for the expression of genes involved in thermotolerance.